Medullary carcinoma of thyroid mimicking Hurthle cell neoplasm on cytology: a diagnostic dilemma. Issue 9 (13th June 2019) - Agarwal, Charu; Raychaudhuri, Sujata; Batra, Ashima; Pujani, Mukta; Dhingra, Shruti
Abstract: Medullary carcinoma of thyroid (MCT) is a neuroendocrine neoplasm derived from the parafollicular cells or C cells. It constitutes 5% of thyroid carcinomas. We present a case of 36‐year‐old female with a left lower lobe thyroid swelling since 8 to 9 years. Swelling was smooth, nontender, and moving with deglutition. Contrast‐enhanced computed tomography (CECT) findings were suggestive of malignant thyroid nodule. Fine‐needle aspiration cytology (FNAC) smears were highly cellular comprising predominantly Hurthle cells arranged in sheets, clusters, and follicles with few singly scattered cells. Background was hemorrhagic with scant colloids. An impression of follicular neoplasm or suspicious of follicular neoplasm was given with an additional note mentioning that the possibility of Hurthle cell neoplasm could not be excluded. Left hemithyroidectomy was done and sections showed a well‐circumscribed tumor suggestive of MCT, which was confirmed based on immunohistochemistry for calcitonin and carcinoembryonic antigen. It is difficult to differentiate MCT from Hurthle cell neoplasm. There may be cellular pleomorphism within a single aspirate, but the presence of mixed cell population is a diagnostic pointer for MCT. In the presence of predominant Hurthle cell population, distinguishing these entities by cytomorphology alone is difficult. Hence, clinical findings and histopathology with immunohistochemistry are mandatory in such cases to reach to a correct diagnosis to ensure proper management.